Cyber Fraud pada Transaksi Game Online melalui Perantara dalam Perspektif UU ITE - Ayugaez, Femanoa Zakia; Luthfillah Arrizqi Zainsyah (Indonesian Journal of Criminal Law, 2025)
The development of information technology in the digital age has brought significant changes to people's activities, including in the fields of entertainment and internet-based economic transactions. Online games now serve not only as a medium for recreation, but also as part of the digital economy through the buying and selling of accounts, items, and virtual currencies. This development has encouraged the emergence of third parties as transaction intermediaries, but at the same time has increased vulnerability to cybercrime, particularly cyber fraud, such as fraud in the sale and purchase of Mobile Legends accounts using illegal escrow services. This study applies a normative legal method with a legislative, conceptual, and case study approach, referring to Law Number 1 of 2024 concerning Electronic Information and Transactions and the Criminal Code in analyzing the perpetrator's responsibility. The findings of the study indicate that cyber fraud in online game transactions through illegal intermediaries can be subject to sanctions based on Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the ITE Law and Article 378 of the Criminal Code. However, challenges in digital evidence, categorizing cyber activities, and determining the liability of intermediaries remain obstacles in law enforcement. Therefore, strengthening technical regulatory mechanisms, enhancing digital literacy, and adopting more adaptive legal interpretations are necessary to ensure optimal user protection.